2018
DOI: 10.1016/j.earscirev.2017.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Global Boundary Stratotype Section and Point (GSSP) for the Anthropocene Series: Where and how to look for potential candidates

Abstract: The Anthropocene as a potential new unit of the International Chronostratigraphic Chart (which serves as the basis of the Geological Time Scale) is assessed in terms of the stratigraphic markers and approximate boundary levels available to define the base of the unit. The task of assessing and selecting potential Global Boundary Stratotype Section and Point (GSSP) candidate sections, a required part of the process in seeking formalisation of the term, is now being actively pursued. Here, we review the suitabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
163
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 178 publications
(168 citation statements)
references
References 287 publications
(415 reference statements)
1
163
0
4
Order By: Relevance
“…Accompanying data of radiocarbon activity (relative to modern 14 C) annual lamina thickness and oxygen and carbon stable isotope data for this speleothem scaled to the lamina age. (Modified from Waters et al ., . )…”
Section: Annual Layering and Cyclical Variations As A Precise Chronommentioning
confidence: 97%
See 2 more Smart Citations
“…Accompanying data of radiocarbon activity (relative to modern 14 C) annual lamina thickness and oxygen and carbon stable isotope data for this speleothem scaled to the lamina age. (Modified from Waters et al ., . )…”
Section: Annual Layering and Cyclical Variations As A Precise Chronommentioning
confidence: 97%
“…Timeline showing the range of suitability of specific radiogenic dating techniques and marker events, including example bomb spikes and volcanic eruptions. (Modified from Waters et al ., . )…”
Section: Radiometric and Radiogenic Dating Techniquesmentioning
confidence: 97%
See 1 more Smart Citation
“…Indeed, efforts are now being made to test potential GSSPs (Global Boundary Stratotype Section and Points) and auxiliary sections, through the study of biological invasions, geochemical signatures and technofossils, allowing the correlation of broader stratigraphical datasets within the Anthropocene (Waters et al . ).…”
mentioning
confidence: 97%
“…Bhandari et al, (2011) [19] reported that GDP at the district level is significantly explained by night lights in the area. Waters et al, (2018) [20] have expressed that the anthropocene epoch is potential to find a place in the International Chronostratigraphic Chart (ICC).…”
mentioning
confidence: 99%